(untitled) (Scientific journal of the Fergana State University, 2026)
In the article, the theoretical foundations of the socio-philosophical research of the dialectic of the change of moral values in the postmodern society, the dialectical analysis of the change of moral values in the postmodern society, the formation of the moral values of the postmodern society and the perspectives of the approach to it are studied. Also, the essence, scientific and conceptual foundations of the concept of "Postmodern society" are analyzed.